Peran Organisasi Aisyiyah Dalam Meningkatkan Pengamalan Pendidikan Islam Indonesia - Aisyatul Munawaroh; Septiani, Novila Mita; Asriadi, Asriadi (Masterpiece: Journal of Islamic Studies and Social Sciences, 2024)
The aim of this research is to analyze the role of "Aisyiyah in improving the practice of Islamic education in Indonesia". This research uses library research, data collection techniques based on related journalsand expert opinions. The data analysis technique used is qualitative descriptive analysis. The results of this research indicate that the Aisyiyah organization was founded on May 19, 1917 AD. This organization began with the Sopo Tresno recitation association which was founded by K.H Ahmad Dahlan and Siti Walidah. The educational views of K.H Ahmad Dahlan and Siti Walidah who feel that it is important for women to get aneducation. Frobelschool is the first educational institution in Indonesia founded by indigenous peoples. Through the ABA Kindergarten which was pioneered by the Aisyiyah Organization, the Indonesian people have succeeded in preparing the nation's next generation for an even better future.